2015
DOI: 10.1177/0162353215607326
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, Cognitions, and Well-Being

Abstract: In this study, we examined interrelationships among emotional overexcitability, perfectionism, emotion regulation, and subjective well-being. Dabrowski and Piechowski’s theoretical conceptualization of overexcitabilities and J. J. Gross and John’s constructs of emotion regulation strategies provided a framework to guide hypotheses in the present study. Participants were 191 adults who responded to surveys administered via online methodology. Multiple-regression analyses revealed that participants in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A previous study also found a positive link between maladaptive perfectionism and depression [32]. Contrastingly, high trait EI is linked to adaptive perfectionism, as hinted by Perrone-McGovern et al [33]. Due to a low emphasis on evaluation by others, individuals with adaptive perfectionism are more resilient toward negative evaluation [34,35], making them less critical when encountering failure.…”
Section: Ei and Perfectionismmentioning
confidence: 85%
“…A previous study also found a positive link between maladaptive perfectionism and depression [32]. Contrastingly, high trait EI is linked to adaptive perfectionism, as hinted by Perrone-McGovern et al [33]. Due to a low emphasis on evaluation by others, individuals with adaptive perfectionism are more resilient toward negative evaluation [34,35], making them less critical when encountering failure.…”
Section: Ei and Perfectionismmentioning
confidence: 85%
“…relationships; however, it can also operate negatively by increasing neurotic selfabsorption (Harrison & van Haneghan, 2011;Mendaglio & Tillier, 2006). Despite the potential negative valence of emotional overexcitability, in general, this overexcitability trait is associated with greater emotion regulation and well-being (Perrone-McGovern et al, 2015).…”
Section: Journal Of Anomalous Experience and Cognition (Jaex)mentioning
confidence: 99%
“…Personal meaning could help sustain students' engagement in school (Brigandi et al, 2016). Students who pursued goals were more self-regulating (Perrone-McGovern et al, 2015) and more likely to tie education to their futures (Brigandi et al, 2016). But the focus remained limited to in-school activities rather than a wider life perspective.…”
Section: Life Purpose In Academically Gifted Youthmentioning
confidence: 99%